Virtual City as a Place for Educational and Social Activities - Fominykh, Mikhail; Prasolova-Førland, Ekaterina; Morozov, Mikhail; Gerasimov, Alexey (International Journal of Emerging Technologies in Learning (iJET), 2009)
In recent years, virtual worlds have become increasingly popular in education and social life. Using a â??cityâ?? metaphor, we are developing a 3D virtual world enriched with social and educational tools. This virtual world allows performing a number of activities, such as exploring the city, learning and communicating with its citizens, building a social network. In this paper we report the results of case studies we have performed to explore usersâ?? activities and behavior in a virtual city context. Our goal was to investigate how such a city can facilitate learning and socializing, also in a cross-cultural context. Based on the empirical results, we derive a list of recommendations for a virtual city as a place for social and educational activities.